Chromaticity stability of beta-carotene from pumpkin (Cucurbita Moschata) - Othman, Rashidi; Abu Bakar, Ainaa Eliah; Mahmad, Noraini; Shahidan, Norshazila (Science Publishing Corporation Inc, 2018)
This study focused on the chromaticity of Beta-carotene extracted from pumpkin (Cucurbita moschata) by using extracts of ethyl acetate. Beta-carotene was then being dissolved in the PLA coating solution and was then being tested with different treatments which were UV-A exposed and different temperature within a period of time. For UV-A, beta-carotene was exposed until 8 hours, while for the different temperature (-25°C, RT, and 40°C), it was exposed until 6 hours. For the CIElab result, the colour changes due to the beta-carotene being exposed under a UV-A light and showed the result was sensitive to UV-A light exposure. For a different temperature, it can be concluded that it was a slightly different within the temperatures selected due to the Beta-carotene was stable with the temperatures, even though it was exposed for a longer time. As a conclusion, it can be said that beta-carotene was sensitive and not stable with the light especially rather than the temperature.